2016
DOI: 10.13065/jksdh.2016.16.05.725
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among oral health behavior, oral health knowledge and dietary control of university students

Abstract: Objectives:The purpose of the study was to investigate the influencing factors of oral health behavior and oral health awareness of university students by assessing oral health practice. Methods: A self-administered questionnaire was completed by 500 university students in Jeonbuk from June 2 to 15, 2014. Except ten incomplete answers, 490 data were analyzed. The questionnaire consisted of general characteristics of the subjects, subjective oral health status (8 items), oral health knowledge (18 items), and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As a college student, it is necessary to establish proper health care habits and take responsibility for health physically, mentally, and socially. However, indifferent behaviors and attitudes can be the cause, making it difficult to form good health habits 9) . At this time, correct health care habits can be linked to the elderly which can affect oral health 10) , and social attention is needed to ensure that correct health care habits are formed in college 9) .…”
Section: Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a college student, it is necessary to establish proper health care habits and take responsibility for health physically, mentally, and socially. However, indifferent behaviors and attitudes can be the cause, making it difficult to form good health habits 9) . At this time, correct health care habits can be linked to the elderly which can affect oral health 10) , and social attention is needed to ensure that correct health care habits are formed in college 9) .…”
Section: Considerationmentioning
confidence: 99%
“…However, indifferent behaviors and attitudes can be the cause, making it difficult to form good health habits 9) . At this time, correct health care habits can be linked to the elderly which can affect oral health 10) , and social attention is needed to ensure that correct health care habits are formed in college 9) . Therefore, this study identified differences in the perceptions between health and non-health students to determine how much college students in their 20s perceived the scaling health insurance benefit business and it was conducted to improve the importance and necessity of scaling, oral health concerns, and to provide basic data on oral health policy, as a way for preventive scaling health insurance benefits to maintain oral health.…”
Section: Considerationmentioning
confidence: 99%